2007
DOI: 10.1016/j.ymeth.2006.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackievirus-induced myocarditis in mice: A model of autoimmune disease for studying immunotoxicity

Abstract: Excellent animal models are available of virus-induced and autoimmune heart disease that are remarkably similar to human disease. Developing good animal models for heart disease is crucial because cardiovascular disease is now the leading cause of death in the United States and is estimated to be the leading cause of death in the world by the year 2020. A significant proportion of heart disease in Western populations is associated with inflammation. Myocarditis, or inflammation of the heart muscle, is the majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
188
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 176 publications
(193 citation statements)
references
References 31 publications
2
188
1
2
Order By: Relevance
“…The lack of models that recapitulate the complexity of the GI tract has hindered studies into many aspects of enterovirus infection in this specialized environment. Although murine models have been developed for the study of enterovirusinduced disease (1)(2)(3)(4), many of these models require intraperitoneal (i.p.) infection, thereby bypassing the GI tract, or require ablation of the host innate immune system (5,6).…”
mentioning
confidence: 99%
“…The lack of models that recapitulate the complexity of the GI tract has hindered studies into many aspects of enterovirus infection in this specialized environment. Although murine models have been developed for the study of enterovirusinduced disease (1)(2)(3)(4), many of these models require intraperitoneal (i.p.) infection, thereby bypassing the GI tract, or require ablation of the host innate immune system (5,6).…”
mentioning
confidence: 99%
“…In the present investigation, an isolate of coxsackievirus B3 (CVB3) originally obtained from a patient was passaged through the heart of BALB/c mice to produce a viral stock that contains cardiac myosin and virus (9). Acute myocarditis develops from days 7 to 14 postinfection (p.i.)…”
mentioning
confidence: 99%
“…and progresses to chronic myocarditis and dilated cardiomyopathy from day 28 p.i. (9). Previously we showed that TLR4 signaling increases myocarditis and IL-1␤/IL-18 levels in the heart following CVB3 infection in male BALB/c mice (10), whereas inflammation is controlled by T cell Ig mucin (Tim)-3 signaling and regulatory T cell populations (Treg) (11).…”
mentioning
confidence: 99%
“…6 -8 Both cellmediated and antibody-mediated immunity contribute to the final pathological picture of chronic inflammation and DCM in EAM and CVB3-induced myocarditis. 9,10 We previously demonstrated that EAM in A/J mice carry hallmarks of Th2-like pathology. Blockade of interleukin (IL)-4 partially suppresses the development of EAM, indicating that IL-4 is cardiopathogenic in this strain.…”
mentioning
confidence: 99%